A polyketide synthase catalyzes the last condensation step of mycolic acid biosynthesis in mycobacteria and related organisms - Portevin, Damien (National Academy of Sciences, 2004)
Mycolic acids are major and specific constituents of the cell envelope of Corynebacterineae, a suborder of bacterial species including several important human pathogens such as Mycobacterium tuberculosis, Mycobacterium leprae, or Corynebacterium diphtheriae. These long-chain fatty acids are involved in the unusual architecture and impermeability of the cell envelope of these bacteria. The condensase, the enzyme responsible for the final condensation step in mycolic acid biosynthesis, has remained an enigma for decades. By in silico analysis of various mycobacterial genomes, we identified a candidate enzyme, Pks13, that contains the four catalytic domains required for the condensation reaction. Orthologs of this enzyme were found in other Corynebacterineae species. A Corynebacterium glutamicum strain with a deletion in the pks13 gene was shown to be deficient in mycolic acid production whereas it was able to produce the fatty acids precursors. This mutant strain displayed an altered cell envelope structure. We showed that the pks13 gene was essential for the survival of Mycobacterium smegmatis. A conditional M. smegmatis mutant carrying its only copy of pks13 on a thermosensitive plasmid exhibited mycolic acid biosynthesis defect if grown at nonpermissive temperature. These results indicate that Pks13 is the condensase, a promising target for the development of new antimicrobial drugs against Corynebacterineae.